Checklist of Mammals of Syria - Aidek, Ahmad E.; Ibrahim, Amir; Amr, Zuhair; Hutterer, Rainer; Kryštufek, Boris; Serra, Gianluca; Benda, Petr; Shkaky, Yesra; Barbanera, Filippo; Al-Sheikhly, Omar F. (Zootaxa, 2025)
A checklist of the wild mammals of Syria including their current status and geographical distribution is provided. Data related to 110 mammalian species were collected following a comprehensive review of available literature records, grey data, and online observations combined with photographic evidence and in situ surveys carried out between 2006 and 2023. The checklist comprises seven orders, 36 families, 73 genera (subgenera), and 110 species, and includes data on 15 globally threatened species of wild mammals. Overall, we report up-to-date information on taxonomic revisions, historical and current geographical range, as well as the conservation status recently assessed by the International Union for Conservation of Nature (IUCN) for one species of hyrax, two lagomorphs, 36 rodents, eight insectivores, 27 chiropterans, 20 carnivores, seven terrestrial artiodactyla, and nine cetaceans.